Processo criativo e análise da recepção da obra Mulheres visíveis: uma entrega pra você! - Mendes, Maria Antonieta Vilela (2024)
This research is dedicated to the process of creation and analysis of scenic work entitled "Visible women: a delivery for you!", consists of performing performances in the form of "dance deliveries'” that embodying stories of women who have suffered some kind of violence. The study investigates beyond the creative process, the capacity that the scenic work has to raise awareness of violence against women, from the presentation of contemporary dance performances in subway stations of the Federal District and subsequent dialogue with the interlocutor public. Considering that the research deals with issues of gender, raciality and creation process, the methodology of performative-qualitative research has been presented as an important methodological instrument for dealing with practice as a research guide.